In Azospirillum brasilense, mutations in flmA or flmB genes affect polar flagellum assembly, surface polysaccharides, and attachment to maize roots - Rossi, Fernando Ariel (2016)
Azospirillum brasilense is a soil bacterium capable of promoting plant growth. Several surface components were previously reported to be involved in the attachment of A. brasilense to root plants. Among these components are the exopolysaccharide (EPS), lipopolysaccharide (LPS) and the polar flagellum. Flagellin from polar flagellum is glycosylated and it was suggested that genes involved in such a posttranslational modification are the same ones involved in the biosynthesis of sugars present in the O-antigen of the LPS. In this work, we report on the characterization of two homologs present in A. brasilense Cd, to the well characterized flagellin modification genes, flmA and flmB, from Aeromonas caviae. We show that mutations in either flmA or flmB genes of A. brasilense resulted in non-motile cells due to alterations in the polar flagellum assembly. Moreover, these mutations also affected the capability of A. brasilense cells to adsorb to maize roots and to produce LPS and EPS. By generating a mutant containing the polar flagellum affected in their rotation, we show the importance of the bacterial motility for the early colonization of maize roots.